Interleukin IL1a and IL6 gene polymorphism: search for association with APOE genotype and clinical course of sporadic Alzheimer’s disease - Pšemeneckienė , G.; Petrikonis , K.; Rastenytė , D. (Neurologijos seminarai, 2019)
Background. There is evidence that genetic polymorphisms of important proinflammatory cytokines IL1α and IL6 are associated with the risk of Alzheimer’s disease (AD). In this study, we aimed to evaluate the association of IL1A -889C>T and IL6 -174G>C polymorphisms with the risk of sporadic AD in APOE ε4 carriers and in persons without APOE risk allele. We also investigated the association of IL1A -889C>T and IL6 -174G>C polymorphisms with the rate of AD progression.Materials and methods. The study included 110 patients with sporadic AD and 115 age-and-gender-matched healthy controls (HC) without cognitive decline (Lithuanian population). Genotyping of IL1A -889C>T (rs1800587) and IL6 -174G>C (rs1800795, Intron type) was performed using real-time PCR (RT-PCR).Results. The distribution of IL1A -889C>T genotypes did not differ between APOE ε4 carriers (APOE4+: C/C – 52.9%, C/T – 41.2%, T/T – 5.9%) and APOE negative AD patients (APOE4-: C/C – 55.6%, C/T – 37.0%, T/T – 7.4%; p=0.887). IL6 -174G>C genotype frequencies in APOE4+ (G/G – 11.8%, G/C – 62.7%, C/C – 25.5%) and APOE4- (G/G – 14.8%, G/C – 61.1%, C/C – 24.1%) were also similar (p=0.898) in AD group. No significant differences of genotype frequencies in rapidly progressing AD compared to slowly progressing AD were revealed (p (IL1A -889C>T)=0.638; p (IL6 -174G>C)=0.118). Controlling by APOE4 status, the inheritance of IL1A -889C>T or IL6 -174G>C polymorphisms (dominant, overdominant, and recessive models) did not significantly alter the odds ratio for sporadic AD (pT and IL6 -174G>C polymorphisms had no significant impact on AD risk (pT and IL6 -174G>C genotype frequencies were found either between groups according to the APOE ε4 allele possession or in patients with rapidly progressing AD compared to slowly progressing AD patients. No significant associations of IL1A -889C>T and IL6 -174G>C polymorphisms and AD risk were revealed in either APOE4 positive or APOE4 negative persons. According to our data, inheritance of IL1A -889C>T and IL6 -174G>C polymorphisms is not associated with faster progression of AD.
Keywords: Alzheimer’s disease; IL1A; IL6; polymorphism; APOE